Can Spore Articles be Used Whithout Permission ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Joaish Mshuda of Dodoma Environmental Network, Tanzania:'We read with interest your article Satisfying needs for milk in urban Africa in Spore 66. We have translated the article into Kiswahili for use in our newsletter Mazingira Yetu - Our...